PPTTG PENERAPAN MESIN PENGUPAS BAWANG MERAH DI DESA SUMBERJO KECAMATAN GONDANG KABUPATEN NGANJUK - Nila Nurlina (UPPM Politeknik Gorontalo, 2019)
Red onion is one of the featured product in Nganjuk. Red onion are a spice that most be present in every food. Red onion is a superior product of Sumberjo Village, Gondang District, Nganjuk Regency because of its fertile agricultural land, and red onion are the main cooking spices of Indonesian people. Sumberjo village has five farmer groups, three of which are partners in the PPTTG, namely Sumber Rejeki, Sumber Makmur, and Tunas Tani farmer groups. This creative farmer group is tasked with setting an example and protecting the farmers of Sumberjo Village so that they can continue to increase their income and manage their agricultural products. The problems faced by the farmer groups are the absence of final product innovations in the context of anticipating a plummeting selling price and poor yield of red onion, low knowledge and skills of the farmer groups in the application of appropriate technology. In this public service program it produces an onion processing machine, one of which is discussed in this paper is the onion peeler machine. The capacity of the machine is 5 kg with a stripping time of 5 minutes. In addition to being given machinery, the farmer group was also given a workshop on business management, machine maintenance, and operational assistance for operating the machine..